Study of Sustainability Irigation System - Melchior Bria; Sutirto Sutirto; Anastasia H. Muda (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2019)
One important indicator in the sustainability of irrigation systems is the reliability of irrigation buildings. Some important factors that can influence it are building operations, building maintenance, community participation, and the value of benefits. This article discusses how the influence of each of these factors on the reliability of irrigation buildings. This study was conducted at Haliwen small dam Reservoir in Atambua NTT. The approach used is structural equation modeling (SEM) with WarpPLS. The results of the analysis show that the variables of operation, maintenance and benefit values have a significant effect on the reliability of mall dam reservoir, while community participation does not directly influence the reliability of small Dam reservoir and the analysis also confirm that to obtain a good value of benefit is highly dependent on community participation in operations and maintenance.